Jogo na rota que eu quiser: uma netnografia sobre a prática do jogo League of Legends por mulheres no Brasil - ARTIGA, Benjamim Tannus (2022)
Electronic games or “video games” have received increasing attention worldwide as a relevant form of cultural and technological production, where Brazil appears as one of the main markets for this type of product, with an estimated audience of 75 million players. With participation in constant growth during the last years, the women are the main consumers of electronic games, however, despite the majority female participation takes place mainly in games considered to be “casual” and not competitive, such as mobile games and developed with themes that with themes that represent a stereotypical performance of what it means to be a woman. On the other hand, in the segment electronic games considered serious or Hardcore, their participation remains reduced. The barriers faced by women in accessing this segment of games have been widely studied by the academic community since the early years of this industry, in studies that point to the construction of gender roles in technology, machismo and regressive masculinity as the main factors for this exclusion. However, even with the various existing barriers to entry, there have always been female players practitioners of games in the hardcore segment, and their growing participation makes them increasingly noticed by the media and industry as a whole, bringing the need to changes that reflect your preferences. This research contributes to the understanding of this public, focusing on the circumstances that led them to practice their favorite game and the meanings that they find in it. A Netnographic research with female players of League of Legends in Brazil, was chosen, focusing on their interactions with the game, using the lens of Theories of Practice, gender roles, and feminist theory. The results show how the previous construction of gender performance and roles associated with it affect its practice, from the circumstances of its access and learning to the choice of functions that will perform and the characters who represent them.